First Eye Cataract Surgery and Hospitalization from Injuries Due to a Fall: A Population-Based Study - Meuleners, Helen; Lee, Andy; Ng, Jonathon; Morlet, Nigel; Fraser, Michelle (Wiley-Blackwell, 2012)
Objectives: To assess the association between first eye cataract surgery and hospitalization from injuries due to a fall in older adults at the population level. Design: Retrospective population-based study. Setting: Western Australian Hospital Morbidity Data System and Western Australian mortality data. Participants: Six hundred individuals aged 60 and older hospitalized from injuries due to a fall between 2004 and 2008 in Western Australia. Measurements: Hospital admission from injuries due to a fall. Results: Of the 15,295 individuals who underwent cataract surgery in one eye only, 600 (3.9%) were involved in 625 hospital admissions from injuries due to a fall 1 year before (n = 273) or 1 year after (n = 352) first eye cataract surgery; 30% of these hospitalizations were for femoral neck fractures. Poisson generalized estimating equations confirmed 27% more (adjusted risk ratio = 1.27, 95% confidence interval = 1.04–1.56 P = .02) hospitalizations from injuries due to a fall in the year after first eye cataract surgery than in the year before. Conclusion: First eye cataract surgery was associated with more hospital admissions from injuries due to a fall in the year after cataract surgery than in the year before. Further research is needed to determine the underlying causes and reasons.